The Multifunction of CLAVATA2 in Plant Development and Immunity - Pan, Lixia; Lv, Shuo; Yang, Nan; Lv, Yanting; Liu, Zhijun; Wu, Jinbin; Wang, Guodong (Frontiers in Plant Science, 2016)
The CLAVATA2 (CLV2) gene encodes a leucine-rich repeat (LRR) receptor-like protein (RLP), a class of cell surface receptors that lacks a cytoplasmic kinase domain. As such, CLV2 is capable of functioning in concert with additional receptor(s), possibly receptor-like kinase(s), to activate cellular responses upon ligand perception. Accumulating data indicate that CLV2 is implicated in distinct biological processes including plant growth and development as well as innate immunity to microbe and nematode infections. This article focuses on recent advances in our understanding of multiple signaling pathways mediated by multifunctional CLV2 that modulate various physiological processes. The challenges and future perspectives of elucidating the specificity of CLV2-mediated signaling pathways and identifying potential co-receptors and putative ligands for CLV2 are also discussed.